2019
DOI: 10.1038/s41598-019-48404-w
|View full text |Cite
|
Sign up to set email alerts
|

Lateral fluid-percussion injury leads to pituitary atrophy in rats

Abstract: Traumatic brain injury (TBI) causes neuroendocrine dysregulation in up to 40% of humans, which is related to impaired function of the hypothalamo-hypophyseal axis and contributes to TBI-related co-morbidities. Our objective was to investigate whether hypophyseal atrophy can be recapitulated in rat lateral fluid-percussion injury model of human TBI. High-resolution structural magnetic resonance images (MRI) were acquired from rats at 2 days and 5 months post-TBI. To measure the lobe-specific volumetric changes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…It is well known that there is a notable difference in the anatomy and physiology of nonhuman mammals (in particular rodents) and human brains. Manganese-enhanced MRI scans revealed that LFP injury caused a 17% reduction in neurohypophyseal volume in the TBI group as compared to controls 64 , suggesting that TBI leads to pituitary atrophy and may serve as a prognostic biomarker for the post-TBI outcome. No single animal model will ever be able to replicate the complete spectrum of changes in human TBI.…”
Section: Discussionmentioning
confidence: 94%
“…It is well known that there is a notable difference in the anatomy and physiology of nonhuman mammals (in particular rodents) and human brains. Manganese-enhanced MRI scans revealed that LFP injury caused a 17% reduction in neurohypophyseal volume in the TBI group as compared to controls 64 , suggesting that TBI leads to pituitary atrophy and may serve as a prognostic biomarker for the post-TBI outcome. No single animal model will ever be able to replicate the complete spectrum of changes in human TBI.…”
Section: Discussionmentioning
confidence: 94%
“…Basic science and understanding of molecular mechanisms in this area are also lacking in pediatrics. While there are several studies that address pituitary dysfunction following TBI (151)(152)(153)(154)(155)(156)(157), these studies have only been done in adult rats. Greco et al, utilized an adolescent mild rTBI model to examine hypopituitarism following TBI.…”
Section: Hormonalmentioning
confidence: 99%
“…Whole brain slices were imaged using a Zeiss AxioScan microscope (Zeiss, Jena, Germany) under a 10X objective. Lesion volume was quantified by a researcher blind to the experimental conditions using ImageJ software (National Institute of Health, USA, version 1.52k) as previously published [25]. The region of interest (ROI) outlining the CCI lesion was manually drawn in the coronal plane using ImageJ software.…”
Section: Lesion Volume Quantificationmentioning
confidence: 99%